Very-high-cycle fatigue behavior of AlSi10Mg manufactured by selected laser melting: Crystal plasticity modeling. (April 2021) - Zhang, Wenjie; Hu, Yanying; Ma, Xianfeng; Qian, Guian; Zhang, Jiamei; Yang, Zhengmao; Berto, Filippo
Highlights: VHCF studied with crystal plasticity theory. Pores have more signification effect on shortening fatigue life than inclusions. Fatigue highly depends on microstructure, especially inclusions and pores. Residual stress near inclusion is harmful to the fatigue life. Abstract: The high-cycle and very-high-cycle fatigue (VHCF) behaviors of AlSi10Mg alloy produced by additive manufacturing (AM) were studied. A crystal plasticity finite element model (CPFEM) with Voronoi tessellation was developed to simulate the cyclic plastic deformation considering defect effects. Morrow's model and Smith-Watson-Topper (SWT) model were used to predict the fatigue life and the SWT model was in good agreement with the experimental life between 10 5 and 10 9 . CPFEM simulation indicated that the accumulated cyclic plastic strain is significantly increased near a pore than that of an inclusion. The residual stress near an inclusion led to large plastic strain localization, which is harmful to fatigue performance.